2015
DOI: 10.1021/bi501117x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Alkaloid Chelerythrine Induced Aggregation of Human Telomere Sequence—A Unique Mode of Association between a Small Molecule and a Quadruplex

Abstract: Small molecules that interact with G-quadruplex structures formed by the human telomeric region and stabilize them have the potential to evolve as anticancer therapeutic agents. Herein we report the interaction of a putative anticancer agent from a plant source, chelerythrine, with the human telomeric DNA sequence. It has telomerase inhibitory potential as demonstrated from telomerase repeat amplification assay in cancer cell line extract. We have attributed this to the quadruplex binding potential of the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 47 publications
11
22
1
Order By: Relevance
“…Earlier reports suggested that anticancer activity of Chelerythrine, a naturally occurring benzophenanthridine plant alkaloid is associated with its potential ability to inhibit protein kinese C. It is also reported previously that Chelerythrine is recognized by human telomeric DNA and RNA G-quadruplex3453. In the present study we have shown that Chelerythrine not only binds to human telomeric DNA and RNA G-quadruplex it also binds to quadruplex structures formed in the promoter region of oncogenes like BCL2, VEGFA and KRAS.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Earlier reports suggested that anticancer activity of Chelerythrine, a naturally occurring benzophenanthridine plant alkaloid is associated with its potential ability to inhibit protein kinese C. It is also reported previously that Chelerythrine is recognized by human telomeric DNA and RNA G-quadruplex3453. In the present study we have shown that Chelerythrine not only binds to human telomeric DNA and RNA G-quadruplex it also binds to quadruplex structures formed in the promoter region of oncogenes like BCL2, VEGFA and KRAS.…”
Section: Discussionsupporting
confidence: 80%
“…The binding constant (K D ) obtained from ITC is closed to other spectroscopic data. The binding affinity (K A ) of Chelerythrine-quadruplex complexes with promoter sequences (BCL2, VEGF and KRAS) is significantly higher than Chelerythrine binding with human telomeric G-quadruplex53. Interestingly the binding affinities are in good agreement with other potent G-quadruplex binders serving as promising anticancer drug targets57.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…On the basis of Nitidine’s reported interactions with G-quadruplexes, 66 we investigated the effect of Nitidine on the three KRAS promoter G-quadruplexes. As previously reported, 28 the Near-G forms an all-parallel G-quadruplex, while the Mid-G and Far-G form mixed parallel/antiparallel G-quadruplexes, with the Far-G being much weaker than the Mid-G, similar to our analyses of the i-motifs.…”
Section: Resultsmentioning
confidence: 99%